Small and Medium-Sized Towns in the Settlement System of the Russian North: 1939–2020 - Viktor V. FAUZER; Andrey V. SMIRNOV; Tatyana S. LYTKINA; Galina N. FAUZER; Valery A. KLIMENKO (Arctic and North, 2021)
The article examines the settlement system of the Russian North, which was previously determined by decisions of ministries and departments, and now it is changing under the influence of resource corporations' activities. The focus is on small and medium-sized towns that are part of the supporting framework of settlement, ensuring connectivity of the northern territories. The authors analyze the dynamics of population, including urban one, and the population of small and medium-sized cities. The study identifies periods of upward and downward dynamics for each population group and settlements. If the country is drawing the population to the west, then in the North it is concentrated in the Asian part. The article shows that urban settlements were created multifunctional, with the monopoly of a city-forming enterprise, which, on the one hand, made them economically vulnerable, and on the other hand — more adaptable to external conditions. According to the author's methodology, small and medium towns are ranked according to the share of the population of these cities in the total population of the region. The authors have identified four groups of regions that have an insufficient, medium, high and excessive share of the population of small and medium towns; the optimal boundaries of this share are proposed. The authors have identified four groups of regions that have an insufficient, medium, high and excess share of the population of small and medium towns; the optimal boundaries of this share are proposed. The study revealed the similarity (concentration of the population in large cities) and the difference in the structure of settlements in the North (the share of the population living in small and medium urban settlements, is lower in the countryside). The research results will be applied in the development of strategic documents for the development of northern towns.